2022
DOI: 10.3390/w14193145
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Cumulative Selectivity of Polycyclic Aromatic Hydrocarbons in Phytoplankton, Water, and Sediment in Typical Urban Water Bodies

Abstract: To understand the interactions among eutrophication, algal bloom, and POPs (persistent organic pollutants) in freshwater ecosystems, the cumulative selectivity of PAHs (polycyclic aromatic hydrocarbons) in phytoplankton, water, and sediment with different eutrophication level waters were identified in a typical plain river network region located in Nanjing City. Results showed that a total of 33 algal species belonging to 27 genera and 4 phyla were identified in 15 sites of urban water bodies, and most of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Similarly, Ma et al concluded through canonical correspondence analysis that DO, TP, and COD are the key environmental factors influencing phytoplankton [ 18 ]. However, Xia's study indicated that temperature, TN, and TP are the key factors affecting phytoplankton, suggesting variations due to different environmental parameters at the study sites [ 38 ]. Therefore, in our study of the Majiagou River, we recognize the need to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ma et al concluded through canonical correspondence analysis that DO, TP, and COD are the key environmental factors influencing phytoplankton [ 18 ]. However, Xia's study indicated that temperature, TN, and TP are the key factors affecting phytoplankton, suggesting variations due to different environmental parameters at the study sites [ 38 ]. Therefore, in our study of the Majiagou River, we recognize the need to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in industrialization, agricultural practices, and socio-economic development near freshwater systems, contributes with diverse organic pollutants that impacts environmental quality [56]. Among organic micropollutants, PAHs are one of the most abundant in freshwater systems and present toxic properties even at low doses, leading to bioaccumulation in fishes [57], invertebrates [7], and algae [58]. The prevalence of PAHs in freshwater systems poses a significant environmental concern, with their discharge into aquatic environments occurring through various pathways, including atmospheric deposition, runoff, and wastewater inputs [59].…”
Section: Freshwater Systemsmentioning
confidence: 99%
“…Due to their numerous negative impacts and cancer-causing nature, these contaminants are extremely harmful. (Xia et al 2022 ). Due to their noxiousness and abundance in the environment, the Environmental Protection Agency (EPA) has named 16 unsubstituted PAHs as the most aggressive pollutants (Qari and Hassan 2017 ).…”
Section: Introductionmentioning
confidence: 99%